2018
DOI: 10.1007/s12010-018-2901-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antimicrobial Properties of Oleoresin Capsicum Nanoemulsions Formulated with Lecithin and Sucrose Monopalmitate

Abstract: Oleoresin capsicum (OC) is an extract of chili pepper containing the active agent capsaicin. In this study, OC-loaded nanoemulsions were prepared by microfluidization and stabilized with sucrose monopalmitate (SMP) and lecithin. The difference in size and distribution of droplets determined the nanoemulsion behavior mainly due to the interaction of emulsifiers between oil and aqueous phase. The hydrophilic interaction between SMP and aqueous phase and the hydrophobic interaction between lecithin and oil phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…With similar reason, AFM measurement gave a larger droplet size of cinnamaldehyde nanoemulsion with Tween 80 than laser dynamic light scattering (Ji et al 2021). Similarly, Akbas, Soyler, and Oztop (2018) and Akbas, Soyler, and Oztop (2019) found that the droplet size of capsicum nanoemulsions with Tween 80 and glycerol, and sucrose monopalmitate (or lecithin) and glycerol, respectively, measured by AFM, was much larger than that observed under TEM. Together with sample preparation, the weak adsorption of the smallest dispersed droplets to the mica surface and the increase in size of nanoparticles caused by the broadening effect of the tip being in contact with soft or sticky biomaterials, were the reasons for the larger droplet size of lemongrass essential oil nanoemulsions with sodium alginate and Tween 80 observed in AFM images, compared with the value determined by TEM or dynamic light scattering (Salvia-Trujillo et al 2013).…”
Section: Characterization Of Nanoemulsions Using Atomic Force Microscopymentioning
confidence: 78%
“…With similar reason, AFM measurement gave a larger droplet size of cinnamaldehyde nanoemulsion with Tween 80 than laser dynamic light scattering (Ji et al 2021). Similarly, Akbas, Soyler, and Oztop (2018) and Akbas, Soyler, and Oztop (2019) found that the droplet size of capsicum nanoemulsions with Tween 80 and glycerol, and sucrose monopalmitate (or lecithin) and glycerol, respectively, measured by AFM, was much larger than that observed under TEM. Together with sample preparation, the weak adsorption of the smallest dispersed droplets to the mica surface and the increase in size of nanoparticles caused by the broadening effect of the tip being in contact with soft or sticky biomaterials, were the reasons for the larger droplet size of lemongrass essential oil nanoemulsions with sodium alginate and Tween 80 observed in AFM images, compared with the value determined by TEM or dynamic light scattering (Salvia-Trujillo et al 2013).…”
Section: Characterization Of Nanoemulsions Using Atomic Force Microscopymentioning
confidence: 78%
“…Figure 2. Atomic force microscopy [ 24 ] was used to confirm the size and shape of the particles (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…Another potential novel application of pepper antioxidants is in the food and pharmaceutical industries. For instance, Akbas et al (2019) used food-grade surfactants, such as sucrose monopalmitate or lecithin, to formulate oleoresin capsicum-loaded nanoemulsions and observed that lecithin-containing nanoemulsions exhibited higher antioxidant and antimicrobial activity, whereas the sucrose monopalmitate-containing nanoemulsions were more transparent, had smaller drop size (about 34 nm), and increased stability when stored with glycerol at ambient temperature for 28 days. Similarly, the acetone extract of pepper (C. annuum) with high antioxidant activity, antimicrobial activity, and phenolics and vitamin C contents was also found to be a potential pharmaceutical coloring and preservative additive in multivitamin candy formulations for kids (Al Khalaf et al, 2020).…”
Section: Novel Product Formulations Of Pepper Antioxidantsmentioning
confidence: 99%